PELAKSANA PERJANJIAN LISAN SEWA KAMAR KOS DI KELURAHAN TELADAN BARAT, KECAMATAN MEDAN KOTA, KOTA MEDAN - Nurasiah Harahap (Universitas Islam Sumatera Utara, 2020)
AbstractLease agreements are agreements arising from the Law, which are regulated in Pasal 1548 to 1600 KUHPerdata. The implementation of the verbal agreement on room rentals in Teladan Barat, Medan City District, Medan City is a consensual agreement. This research is a descriptive analysis which is to present an overview of the implementation, barriers and how to overcome obstacles in the verbal agreement of rent a room.The provisions of the room rental agreement made verbally in Teladan Barat Village, Medan City District, Medan City, are in accordance with Pasal 1233 KUHPerdata. Implementation of verbal agreement to rent a room is considered valid if there is an agreement on the room and the price, the parties have the rights and obligations that must be implemented. But in practice there are obstacles and problems.It can be concluded that the implementation of verbal agreement on room rent in Teladan Barat Village, Medan District, Medan City found different opinions from respondents and the implementation of the agreement regarding obstacles and problems was no clarity because it was made verbally and the constraints of the number of migrants for data collection for the head of the village. Keywords : Verbal agreement, room rent, Teladan Barat Village, Medan District, Medan City